Assessment of similarity and self-other agreement in dyadic relationships: A guide to best practices. (January 2018) - Rogers, Katherine H.; Wood, Dustin; Furr, R. Michael
Many questions within the relationship literature are concerned with the similarity between individuals or the agreement of perceptions. There are a number of different methods used to assess these questions (e.g., correlation, profile correlation, and squared difference scores), and there are special considerations that need to be included when analyzing data of this sort (e.g., correction for mean levels). We provide an overview of when these different methods are most appropriate and recommendations for applying the different statistical techniques. We also include an example data set to demonstrate how these analyses should be performed and how results may differ based on the techniques used.